1974
DOI: 10.1017/s0007485300047817
|View full text |Cite
|
Sign up to set email alerts
|

The range of attraction of birds as baits for Some West African mosquitoes (Diptera, Culicidae)

Abstract: The long range orientation of West African mosquitoes to birds was studied using ramp-traps set up 3–23 m from the bait. The baits comprised chickens, ducks, pigeons and the carbon dioxide equivalent of the chickens. From the pattern of convergence of mosquitoes to the baits, it was shown that Anopheles melas Theo. and Culex thalassius Theo. were orienting to all the bird-baits from distances of at least seven metres. Responses to carbon dioxide were only apparent at a distance of three metres indicating the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 7 publications
0
17
1
Order By: Relevance
“…In Florida Edman (1979) used ramp traps similar to those of Gillies (1969) to study host orientation to animal baits and carbon dioxide. Contrary to the observation of Gillies & Wilkes (1974) he found no evidence that host-seeking mosquitoes fly downwind, in fact Culex nigripalpus exhibited strong upwind flight. It appeared that hosts, or carbon dioxide, stimulated host-seeking at a distance of 15 m. Another approach is to place two identical traps at varying distances from each other, and then determine at what distance the size of the catch per trap is no longer decreased by the other, this would then be equal to twice the trap's range of attraction.…”
Section: General Considerationscontrasting
confidence: 88%
“…In Florida Edman (1979) used ramp traps similar to those of Gillies (1969) to study host orientation to animal baits and carbon dioxide. Contrary to the observation of Gillies & Wilkes (1974) he found no evidence that host-seeking mosquitoes fly downwind, in fact Culex nigripalpus exhibited strong upwind flight. It appeared that hosts, or carbon dioxide, stimulated host-seeking at a distance of 15 m. Another approach is to place two identical traps at varying distances from each other, and then determine at what distance the size of the catch per trap is no longer decreased by the other, this would then be equal to twice the trap's range of attraction.…”
Section: General Considerationscontrasting
confidence: 88%
“…Furthermore, application of CO 2 in the field is costly; it needs to be transported into the field in pressurized gas cylinders or as dry ice (Bernier et al, 2003;Curtis, 1996;Knols et al, 1994;Knols et al, 1998;Mboera et al, 2000). By contrast, the use of human-associated kairomones is considered as a good alternative method for collecting, monitoring or controlling host-seeking mosquitoes, as these in a series of behavioral tests in the laboratory and field have shown to elicit high levels of attraction without the presence of CO 2 (Bernier et al, 2003;Edman, 1979;Eiras and Jepson, 1991;Eiras and Jepson, 1994;Gillies and Wilkes, 1974;Silva et al, 2005). The use of GC-SSRs and other analytical methods will be valuable for selecting additional kairomone compounds to optimize an attractive bait.…”
Section: Discussionmentioning
confidence: 99%
“…The temperatures in the two arms of the olfactometer were identical, so the mosquitoes were not attracted to the human hand arm of the olfactometer because of differences in that. Nor does it seem that carbon dioxide could have been a major factor since this is known to attract mosquitoes (Gillies & Wilkes, 1969, 1974), yet less Ae.aegypti went to the rat arm which included the rat's exhaled air, whereas the arm containing the human hand did not. Nor again, does it seem likely that humidity differences could have been very important, since Brown (1951Brown ( , 1958 showed that dummies whose clothing was soaked with human sweat were significantly more attractive to Aedes in the field than controls with equally moist clothing.…”
Section: Discussionmentioning
confidence: 99%